Gender wage differentials in Singapore. - Kwek, Qiao Ping. (2011)
Using Singapore Labour Force Survey data from 1998, we employ unconditional quantile regression based on two different methodologies to analyze gender wage differentials in Singapore. These methods allow for the characterisation of the contribution of any single covariate in a wage distribution. We find evidence of a ‘sticky floor’ typical of most Asian countries.